2005
DOI: 10.1124/jpet.104.081174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Changes in Amyloid-β(40) in the Rat Brain and Cerebrospinal Fluid following Treatment with the γ-Secretase Inhibitor LY-411575 [N2-[(2S)-2-(3,5-Difluorophenyl)-2-hydroxyethanoyl]-N1-[(7S)-5-methyl-6-oxo-6,7-dihydro-5H-dibenzo[b,d]azepin-7-yl]-l-alaninamide]

Abstract: The efficacy of ␥-secretase inhibitors in vivo has, to date, been generally assessed in transgenic mouse models expressing increased levels of amyloid-␤ (A␤) peptide thereby allowing the detection of changes in A␤ production. However, it is not clear whether the in vivo potency of ␥-secretase inhibitors is independent of the level of amyloid precursor protein expression. In other words, does a ␥-secretase inhibitor have the same effect in nontransgenic physiological animals versus transgenic overexpressing ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…We hypothesized that acute depletion of soluble Aβ via γ-secretase inhibition would improve vessel function. We assessed vessel reactivity in young Tg2576 mice in the presence and absence of significant extracellular brain and plasma human Aβ utilizing the blood-brain barrier permeable γ–secretase inhibitor, LY411575 (Cirrito et al, 2003; Best et al, 2005). Similar to previous results (Cirrito et al, 2005b), subcutaneous administration of LY411575 (3 mg/kg) in young Tg2576 mice resulted in almost complete depletion of soluble human Aβ 1-x pool in the interstitial fluid (ISF) up to 36 h after drug administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that acute depletion of soluble Aβ via γ-secretase inhibition would improve vessel function. We assessed vessel reactivity in young Tg2576 mice in the presence and absence of significant extracellular brain and plasma human Aβ utilizing the blood-brain barrier permeable γ–secretase inhibitor, LY411575 (Cirrito et al, 2003; Best et al, 2005). Similar to previous results (Cirrito et al, 2005b), subcutaneous administration of LY411575 (3 mg/kg) in young Tg2576 mice resulted in almost complete depletion of soluble human Aβ 1-x pool in the interstitial fluid (ISF) up to 36 h after drug administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The γ-secretase inhibitor LY-450139 is one of the most potent inhibitors and is currently in phase II clinical trials and it appears to be well tolerated in human Alzheimer’s patients (Siemers et al, 2006). While this inhibitor is the only one currently being tested in humans, other SPP inhibitors, such as LY-411,575 (Eli Lilly), BMS-299,897 (Bristol-Meyers Squibb) and DAPT (Eli Lilly) have been studied for their effect in vivo (Best et al, 2005; Dovey et al, 2001; Siemers et al, 2005; Siemers et al, 2006). In this study we have shown for the first time that SPP chemical inhibitors are able to block HSV-1 infectivity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepine analogue LY-411575 and benzolactam LY-450139, developed at Eli Lilly, are highly potent γ-secretase inhibitors that have been tested extensively in vivo 5658. LY- 411575 is one of the most potent γ-secretase inhibitors yet reported, with an IC 50 of 119 pM for inhibiting Aβ production in APP-overexpressing HEK293 cells.…”
Section: Therapeutic Potential Of γ-Secretase Inhibitors For Admentioning
confidence: 99%